The Emerging Environmental and Public Health Problem of Electronic Waste in India - Joon, Veenu (J Health Pollut, 2017)
BACKGROUND. Monumental progress has been made in the area of information and communication technology, leading to a tremendous increase in use of electronic equipment, especially computers and mobile phones. The expansion of production and consumption of electronic equipment along with its shorter life span has led to the generation of tremendous amounts of electronic waste (e-waste). In addition, there is a high level of trans-boundary movement of these devices as second-hand electronic equipment from developed countries, in the name of bridging the digital gap. OBJECTIVES. This paper reviews e-waste produced in India, its sources, composition, current management practices and their environmental and health implications. Fixing responsibility for waste disposal on producers, establishment of formal recycling facilities, and strict enforcement of legislation on e-waste are some of the options to address this rapidly growing problem. DISCUSSION. The exponential growth in production and consumption of electronic equipment has resulted in a surge of e-waste generation. Many electronic items contain hazardous substances including lead, mercury and cadmium. Informal recycling or disposing of such items pose serious threat to human health and the environment. CONCLUSIONS. Strict enforcement of waste disposal laws are needed along with the implementation of health assessment studies to mitigate inappropriate management of end-of-life electronic wastes in developing countries.